Prevalência de lesões em praticantes amadores de futebol - Mariano, Felipe (2021)
Although soccer is considered a leisure activity that can improve health, as it is a contact sport, it is also associated with a higher risk of injury. The objective of this study was to identify the frequency and characterization of injuries in amateurs (recreational) who play soccer in Curitiba and to identify possible risk factors, based on a descriptivecorrelational study, through a self-administered questionnaire applied to practitioners. For data analysis, descriptive statistics was performed, as well as a logistic regression analysis between the dependent variable (lesion) and the independent variables observed in the study with a significance level of 5% (p<0.05). Of the 100 players (age; 24 ± 5.7 years, BMI; 24.9 ± 3.3 kg/m²; practice time 3 ± 0.37 years) interviewed, 29% reported injuries. The results obtained in this research show that the most frequent injuries are: muscle strain (31.03%) followed by ligament injuries (20.69%) of the lower limbs and muscle contracture (10.34%). Regarding injuries reported in the last 12 months, the occurrence of ankle injuries (sprains). A significant association was also observed between the presence of injury and increasing age, weekly practice and BMI. Thus, it is suggested the need to carry out protocols for the prevention of injuries adapted to football, emphasizing measures that intervene in the identified risk factors.